Entre o campo e o núcleo: saberes da prática da Terapia Ocupacional em saúde mental - Melo, Cleber Henrique de (Universidade Federal de São Carlos, 2025)
In the context of mental health care practices, supported by the psychosocial model, Brazilian occupational therapists play a crucial role in promoting collaborative and interdisciplinary practices. Given the continuous evolution of the profession, it is important to investigate the various facets of practice and how they shape the professional core in the field of mental health. The field is understood as a dynamic and collaborative space, and the core as the integration of specific knowledge that defines the profession. Thus, it becomes feasible to advance the discussion on its contours. General Objective: To understand the specific practice of occupational therapy in mental health from the perspective of occupational therapists working in facilities that make up the Psychosocial Care Network (RAPS). Method: This is a non-experimental, cross-sectional, and exploratory-descriptive study, using a convenience sample of 53 occupational therapists working in the Brazilian RAPS. The professionals answered a semi-structured questionnaire with closed and open-ended questions, enabling a sociodemographic overview of the participants and insight into how these professionals interpret and develop their practices in their daily work. Analysis and Results: The qualitative data, obtained from the open-ended questions, were examined using the IRaMuTeQ software, allowing classification into five categories: 1. Articulation of Occupational Therapy with the Field; 2. Foundations of Occupational Therapy in Mental Health; 3. Demands and Objectives of Occupational Therapy in Mental Health; 4. Technical Core of Occupational Therapy; 5. Delineation of the Professional Core. The results show that the discussions within the Brazilian mental health field by occupational therapists have been based on conceptions from the theoretical and methodological frameworks referred to as common clinical practice and collective health. Regarding specific theoretical and methodological aspects, a variety of perspectives on the contours and boundaries of the professional core of occupational therapy in the field of mental health is identified. Conclusion: The construction and strengthening of the professional core of occupational therapy in the field of mental health necessarily involve constant negotiation. There is an emerging need to foster critical thinking that guides the profession beyond rigid dichotomies. Instead of opting for unrestricted adherence or inflexible separation, a dynamic balance is proposed, where the specificity of occupational therapy is upheld by occupational therapists, while its practice expands through dialogue with other areas of knowledge.
Between the field and the core: knowledge from Occupational Therapy practice in mental health
Keywords: Terapia ocupacional; Saúde mental; Competência profissional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL